Eco-friendly quantum dots for liquid luminescent solar concentrators. Issue 4 (3rd January 2020) - Liu, Xin; Luo, Bing; Liu, Jiabin; Jing, Dengwei; Benetti, Daniele; Rosei, Federico
Abstract : Eco-friendly Cu doped Zn–In–Se QDs for liquid luminescent solar concentrators can provide a platform of more efficient and environmentally friendly solar energy harvest systems. Abstract : Luminescent solar concentrators (LSCs) are a promising solution to reduce the cost of integrated photovoltaic (PV) cells. Colloidal quantum dots (QDs) have been shown to be excellent candidates as a new type of absorber/emitter in LSCs, due to their size-tunable absorption and emission, high photoluminescence quantum yield (PLQY) and structure-engineered large Stokes shift. However, to date, the majority of QD-based LSCs employ QDs containing heavy-metal ( e.g. Cd or Pb) elements, which limits the potential commercialization of LSCs. Herein, we propose the synthesis of green transition metal ion-doped semiconductor QDs such as Cu-doped ZnInSe QDs and their use as luminophores in LSCs. By tailoring the amount of Cu doping, it was possible to tune the photoluminescent (PL) emissions over the whole visible spectral window and simultaneously enlarge the Stokes shift, reaching a PLQY of 63%. Furthermore, a comparative study between polymer and liquid solar concentrators showed that, under optimal conditions, it is possible to obtain a green, heavy metal free liquid QD-based LSC with a high optical efficiency of over 3.5%. This result is more than two times higher than that of a polymer LSC ( η opt = 1.75%, G = 10), which could be ascribed to the reduced reabsorption losses and avoided energy loss by surface and internal defects resulting from polymerization. The waveguides for liquid LSCs could be recycled for tuning the concentrations and changing various luminophores which makes the liquid LSCs cost-effective and environmentally friendly. The success of eco-friendly Cu doped Zn–In–Se QDs for liquid LSCs provides a platform of more efficient and environmentally friendly solar energy harvest systems. In addition, the comparative study between liquid and polymer waveguides provides an opportunity to optimize LSC performance.